PENERAPAN METODE PEMBELAJARAN PICTURE AND PICTURE PADAMATERI POKOK SEGITIGA UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR SISWA KELAS VII SMPN 5 KOPANG TAHUN PELAJARAN 2016/2017 - Yunita, Sri; Sukarma, I Ketut; Kurniawan, Ade (Universitas Pendidikan Mandalika (UNDIKMA), 2017)
Based on the results of the initial observation, problem issues that can be secn in the learning process that studentsâ€™ of less passion, attention is less focused and less concentration to absorb the lessons. The aimed of this research is to describe the implementation of picture and picture learning model that able to improve studens activity and learning outcomes at VII Grade studen of SMPN 5 Kopang Tahun pelajaran 2017/2018. The type of this research is class room action research. the data colection are quantitative and qualitatiy data. Based on Â the result of data analysis obtained studen learning outcomens scor is 58,26 at firs cycle and 86,30 at secon cycle. So that it can be con cluded that the implementation of Picture and Picture learning methods able to improve studens activity and learning outcomes at VII Grade studen of SMPN 5 Kopang Tahun pelajaran 2017/2018